Thickness control of thin dielectric layers by the generalized m-line spectroscopy method - Auguściuk, Elżbieta; Bogdanowicz, Bartłomiej (Photonics Letters of Poland, 2010)
This paper presents an application of the generalized m-line spectroscopy method to immediate evaluation of a thin dielectric layer thickness deposited on a waveguide without any numerical calculation. For this purpose, a calibration curve (i.e., dependence of a thin layer thickness on coupling angle of the corresponding mode) shall be determined. It allows determining sample thickness by measuring the coupling angle of the mode. In the present paper it has been shown that multimode waveguides are best for our measurement investigation. The sensor has the greatest sensitivity in the measurement of coupling angles for a higher number of modes. Full Text: PDF References E. Auguściuk, M. Roszko, W. Fabianowski,"Growth control of polymer films deposited on the planar waveguide", Proc. of SPIE 5064, 245 (2003)[CrossRef] E. Auguściuk, F. Sala,"Application of planar waveguides with gradient index profile to determine parameters of thin active layers used in waveguide sensors", Proc. of SPIE 6585, 65852D (2007)[CrossRef] N. Uchida,"Optical waveguide loaded with high refractive-index strip film", Appl.Opt. 15, 179 (1976)[CrossRef] E. Auguściuk, G.Biniecki,"Investigation of parameters of the multimode four-layer waveguide structures and their influence on the light propagation", Phot. Lett. of Poland 1(3), 124 (2009) P. K. Tien, R. Ulrich,"Theory of Prism-Film Coupler and Thin-Film Light Guides", J. Opt. Soc. Am. 60(10), 1325 (1970)[CrossRef] R. Ulrich,"Theory of the Prism-Film Coupler by Plane-Wave Analysis", J. Opt. Soc. Am. 60 (10), 1337 (1970)[CrossRef] P. K. Tien,"Light Waves in Thin Films and Integrated Optics", Appl. Opt. 10 (11), 2395 (1971)[CrossRef] R. Ulrich, R. Torge,"Measurement of Thin Film Parameters with a Prism Coupler", Appl. Opt. 12(12), 2901 (1973)[CrossRef] T. Findakly,"Glass Waveguides by Ion-Exchange: A Review", Optical Engineering 24 (2), 244 (1985) http://pl.wikipedia.org/wiki/Spin- coater E. Auguściuk,"Multilayer waveguide structures investigated by the generalized m-line spectroscopy", Proc. of SPIE 7120, 71200J (2008) [CrossRef]